THE MODERNIZATlON PROCESS Of THE STATE IN ARGENTINA: CHARACTERISTlCS AND PARTICULARITIES Of AN OWN AND INNOVATIVE THOUGHT - Asinelli, Christian; Alvarez Travieso, María Florencia; Yodert, Pablo (Cuadernos de Administración, 2008)
This paper describes the integral strategy of Modernization of the Argentine State (EIME), aimed at achieving a public sector that, focused on the citizen, could be capable of providing quality services and promote economic and social development. This is part of a broader process that begins with the management of president Kirchner, initially conditioned by the 2001 crisis and inheritance of the paradigm of "less state and more market" (Cavarozzi, 1993)of the 90' s. First, the modernization will be addressed from an overall perspective, and then focus the approach in describing the case of Argentina. Here, will discuss the innovative strategy adopted , which conceives the state modernization as a political and social process, with clear technical aspects. They define two phases of implementation aimed at strengthening institutional capacities of a key political player of the system: Head of the Cabinet of Ministers. The work will deepen the experience gathered during 2003-2006, when using the ' strategy focused on Administrative Modernization', are strengthened ' horizontal ' institutional capacities, incorporating tools designed to optimize the quality of management. Overcoming the crisis and consensus reached on the EIM, allowed to launch the "Institutionalization Strategy" (2007-2011), seeking to improve the coordination of state action to fulfill the government Plan.